Formation of Research Area for Malaysian Urban Data Centre and Waste Heat Recovery - Othman M.; Maidin S.S.; Suliman A.; Zakaria N.Z.; Nassar D.; Al-Ghaili A.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Climate change; Climate models; Energy efficiency; Energy utilization; Green computing; Waste heat utilization; Waste treatment; Cooling process; Datacenter; Digital applications; Energy use; Energy-consumption; Malaysians; Operation process; Research areas; Sustainable; Waste-heat recovery; Waste heat